A Study of the Impact of WeChat Groups on Home-school Cooperation in Primary and Secondary Schools in the Era of "Internet+" - Liu , Xiaoyao (Journal of Theory and Practice of Contemporary Education, 2023)
Home-school cooperation is an important part of primary and secondary education. With the advent of the Internet+ era and the popularity of WeChat in China, WeChat groups have gradually become an important tool and means of home-school contact and classroom management, which are commonly used in primary and secondary schools in China, and parent WeChat groups are playing an increasingly important role in primary and secondary schools. From the perspective of home-school cooperation, this paper examines the advantages and disadvantages of WeChat groups for home-school cooperation and explores ways to manage WeChat groups.